Experimental observation of neutron-neutron correlations in nucleus 6He from 3H(α,pα)nn reaction - O. M. Povoroznyk; O. K. Gorpinich (Ядерна фізика та енергетика)
The projections of two-dimensional spectra of p-α coincidences from the four-particle reaction of 3H(α, pα)nn with the energy of alpha-particles 27.2 MeV on the energy axis of alpha-particles for six pairs of angles are analyzed. The results of the Monte Carlo parameterization show that in the case of the decay of the first excited state of 6He, the configuration of the "alpha-particle + dineutron" dominates only in a limited phase-space domain, while in other kinematics and for the second and third excited states, the configurations of "alpha-particles + dineutron" and "alpha-particles + cigars" are present in different ratios.